Mapping of herpes simplex virus 1 genes with mutations which overcome host restrictions to infection. - Brandimarti, R (1994)
Earlier studies have shown that the thymidine kinase-negative baby hamster kidney (BHKTK-) cell lines expressing constitutively the herpes simplex virus 1 (HSV-1) glycoprotein D (gD), designated BJ, restrict infection by HSV-1 at the level of virus entry. U10, a HSV-1 mutant not restricted by the BJ cells, carried the substitution of proline for Leu25 in the gD gene, suggesting that gD encodes a specialized domain which precludes virus entry into cells expressing gD. Analyses of a new series of 36 unrestricted viral mutants showed the following. (i) Only two mutants contained mutations at a site which did not overlap with the previously reported mutation. A representative of a previously mapped mutant and one of the two new mutants were examined in detail. Thus, in the gD of mutant U30 Ala185 was replaced by threonine, whereas in gD of U21, Ala185 and Leu25 were replaced with threonine and proline, respectively. U30 and U21 multiplied better than the wild-type parent virus in the parental BHKTK- cells. (ii) Transfer of the gD gene from U21 or U30 to wild-type parent virus or to the gD- virus FgD beta yielded recombinants which, while capable of infecting BJ cells, were considerably less efficient than the parent unrestricted mutants, suggesting that the latter contained additional mutations which were responsible in part for the unrestricted phenotype. Conversely, marker rescue of mutant viruses with wild-type gD reduced but did not abrogate entirely the unrestricted phenotype. (iii) Mutations in gD which conferred the unrestricted phenotype were not random. (iv) gD plays a role in the restriction, inasmuch as preincubation of cells expressing gD with antibodies to gD abolished restriction. (v) In mutant R5000, the gD substitution Ser140 to Asn was capable of overcoming a restriction of a BHKTK- clonal line which does not express gD but conferred very low ability to replicate on BJ cells. We conclude that (a) uncloned stocks of BHKTK- cells exhibit a low level restriction to infection with wild-type virus, (b) clonal lines of BHKTK- cells which vary with respect to the stringency of restriction express either allelic genes differing in the properties of their products or products of different genes, and (c) both the restricted and unrestricted phenotypes reflect the interactions of gD with these cellular products. The implications of these conclusions with respect to the restriction imposed on BHK cells by the expression of gD are discussed.